DETERMINANTS OF VENTURE CAPITAL EXPANSION: THE IMPACT OF INSTITUTIONS, ECONOMIC DEVELOPMENT, AND MARKET LIQUIDITY (European Journal of Economics, Finance and Business Development, 2026)
This study examines the determinants of venture capital development with a focus on institutional quality, economic development, and market depth of countries. Using unbalanced panel data across countries, the analysis applies advanced econometric techniques, including the Mundlak (Correlated Random Effects) approach, to account for unobserved heterogeneity and distinguish between within- and between-country effects. The results show that GDP per capita and stock market activity positively influence venture capital investment, highlighting the importance of economic development and exit opportunities. While the within-country effect of the rule of law appears negative, its between-country (mean) effect is positive and statistically significant, suggesting that countries with consistently stronger institutional environments attract higher levels of venture capital in the long run. Overall, the findings emphasize that venture capital development is primarily driven by structural differences in institutional quality and market conditions rather than short-term changes. The study provides important policy implications, particularly for emerging economies, underscoring the need to strengthen legal systems, develop exit markets, and support risk-sharing financial mechanisms.